Lithium adsorbent particle as well as preparation method and application thereof
The lithium adsorbent particles with a network structure formed by polypeptide cross-linking address the issues of low bonding strength and hydrophilicity, enhancing lithium extraction efficiency and cycle life.
Patent Information
- Application Number
- CN202411493114.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-24
AI Technical Summary
Existing lithium extraction technologies face issues with low bonding strength between adsorbent powder and polymer binder, leading to reduced cycle life and low hydrophilicity of the adsorbent surface, which affects adsorption capacity and extraction efficiency.
A lithium adsorbent particle composed of lithium adsorbent precursor powder, polypeptide, polymer binder, and porogen, where the polypeptide forms a network structure through chain entanglement and hydrogen bond interactions, enhancing viscosity and hydrophilicity, and self-crosslinking to stabilize the adsorbent.
The improved adsorbent particles exhibit enhanced hydrophilicity, increased effective component ratio, and stronger bonding, resulting in higher lithium extraction rates and improved wear resistance and cycle life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium extraction from salt lakes, and specifically relates to lithium adsorbent particles and a preparation method and application thereof. Background Art
[0002] As the cumulative amount of retired power batteries in my country continues to rise, battery recycling will also usher in a period of rapid development. Overall, whether it is salt lake lithium extraction or battery recycling, high-performance lithium extraction materials and green, efficient and low-cost combined processes will be one of the core of industrial development.
[0003] As the core material in the field of lithium extraction technology, adsorbents usually need to have the following three characteristics: 1) Excellent selective adsorption. Ability to selectively adsorb lithium ions from the solution and pass other ions; 2) Good stability. Ability to maintain good performance, structure, and mechanical stability during repeated adsorption and desorption in a high-salinity environment; 3) High adsorption capacity. A unit mass of adsorbent material can adsorb as many lithium ions as possible.
[0004] In the prior art, CN109225124A discloses a method for preparing a granular lithium adsorbent, wherein a lithium adsorbent or its precursor powder, a plurality of polymers, a pore-forming agent and an organic solvent are mixed and stirred under a certain pressure and temperature to obtain a uniform mixture, and then the uniform mixture is dripped into a solution, or the uniform mixture is extruded and crushed, and then washed to obtain a granular lithium adsorbent. The adsorbent particles prepared by this invention patent have high strength and good toughness, and are suitable for industrial applications. However, this method does not consider the problem of low bonding strength between the adsorbent powder and the high molecular polymer and the loss of powder. CN115845825B discloses a method for preparing a lithium adsorbent, wherein a binder, a pore-forming agent and a precursor powder are mixed in a solvent according to a specific ratio, and pelletized after spin curing to achieve granulation molding of a powdery lithium adsorbent. This invention patent uses water-soluble organic matter of different molecular weights as porogens, and finally confirms that a special gradient pore structure is formed inside the product. This gradient pore is conducive to preventing powder loss and ion transfer, effectively increasing the service life of the adsorbent, and also promoting the acceleration of the adsorption rate and desorption rate. However, this method still has the problem of large amount of polymer binder and weak adhesion between the binder and the powder, which leads to reduced cycle life due to wear of the adsorbent during long-term use. On the other hand, since the hydrophilic porogen is lost in the coagulation bath, the surface of the adsorbent particles is not hydrophilic, which will also cause the adsorption capacity to be not high enough and the lithium extraction rate cannot be further improved.
[0005] Therefore, it is necessary to improve the bonding strength between the binder and the powder and the hydrophilicity of the adsorbent surface to solve the problems existing in the prior art such as large amount of polymer binder used and low hydrophilicity of the adsorbent particle surface. Summary of the invention
[0006] The present invention aims to solve the problems in the existing molding and granulation technology, such as large amount of binder used, low proportion of effective component lithium adsorbent precursor, low hydrophilicity of adsorbent particle surface, low adsorption capacity after granulation, low lithium extraction efficiency, etc., and provides lithium adsorbent particles and their preparation method and application.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a lithium adsorbent particle, which contains lithium adsorbent precursor powder, polypeptide, polymer binder and porogen. The polypeptide cross-links the precursor powder, polymer binder and porogen into a network structure through chain entanglement and hydrogen bond interaction with the polymer binder and porogen, as well as self-crosslinking, thereby enhancing the overall viscosity and surface hydrophilicity of the adsorbent particle.
[0009] Furthermore, the polypeptide is formed by dehydration condensation of 2 to 10 amino acids and has a molecular weight of 200 to 1500.
[0010] Furthermore, the mass ratio of the polypeptide to the polymer binder is 0.1 to 1:1, preferably 0.1 to 0.5:1.
[0011] Furthermore, the mass ratio of the lithium adsorbent precursor powder to the polymer binder is 5 to 50:1, preferably 5 to 20:1.
[0012] Furthermore, the lithium adsorbent precursor powder is selected from LiCl.2Al(OH)3.nH2O, LiMn2O4, Li 1.6 Mn 1.6 O4、Li 1.33 Mn 1.67 O4, Li2TiO3, Li4Ti5O 12 One or more of .
[0013] Furthermore, the particle size of the lithium adsorbent precursor powder is 0.1-100 μm, preferably 1-50 μm.
[0014] Furthermore, the polymer binder is selected from one or more of polysulfone, polyvinylidene fluoride, polyvinyl chloride, chlorinated polyvinyl chloride, cellulose acetate, carboxymethyl cellulose, and chitosan.
[0015] Furthermore, the porogen is selected from one or a mixture of PVP K30, PVP K60, PVP K90, PEG-1000, PEG-2000, and PEG-6000.
[0016] Furthermore, the amount of the porogen is 0.1-5wt% of the weight of the lithium adsorbent precursor powder.
[0017] In a second aspect of the present invention, a method for preparing lithium adsorbent particles is provided, comprising the following steps:
[0018] (1) mixing lithium adsorbent precursor powder, polypeptide, polymer binder, organic solvent and porogen at high temperature to obtain a mixture;
[0019] (2) curing, drying, crushing and screening the mixture to obtain a lithium adsorbent semi-finished product;
[0020] (3) The lithium adsorbent semi-finished product is post-treated with deionized water to obtain lithium adsorbent particles.
[0021] Furthermore, in step (1), the organic solvent is selected from one or a mixture of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, chloroform, dichloroethane, and ethyl acetate. Preferably, the amount of the organic solvent is 50 to 100% of the total mass of the precursor powder, polypeptide, and polymer binder.
[0022] Furthermore, in step (1), the mixing temperature is 80-120° C., and the mixing time is 1-5 h.
[0023] Furthermore, in step (2), the particle size of the lithium adsorbent semi-finished product obtained by crushing and screening is 0.5 mm to 3.0 mm.
[0024] Furthermore, in step (3), the deionized water post-treatment temperature is 25 to 45° C., and the lithium adsorbent semi-finished product is treated at a stirring rate of 20 to 120 r / min for 12 to 48 hours. After filtering to remove excess water, lithium adsorbent particles are obtained.
[0025] In a third aspect, the present invention provides the application of the lithium adsorbent prepared by the above-mentioned preparation method in the technical field of lithium extraction from salt lakes.
[0026] The beneficial effects of the present invention are as follows: the present invention provides a lithium adsorbent particle, which contains a lithium adsorbent precursor powder, a polypeptide, a polymer binder and a porogen. The polypeptide cross-links the precursor powder, the polymer binder and the porogen into a network structure through chain entanglement and hydrogen bond interaction with the polymer binder and the porogen, as well as self-crosslinking, thereby enhancing the overall viscosity and surface hydrophilicity of the adsorbent particles. This is because the polypeptide is formed by the dehydration condensation of multiple amino acid molecules, and can act as a hydrogen donor to form hydrogen bonds with molecules containing hydrogen acceptors. On the other hand, the residual carboxyl and amino groups of the polypeptide can self-crosslink to form peptide bonds under appropriate conditions, which can provide stable and reversible crosslinking points between polymers, thereby realizing crosslinking and self-assembly of polymers.
[0027] In the preparation process of the present invention, the adsorbent precursor powder, polypeptide, polymer binder, and pore-forming agent are uniformly mixed together. When mixed, the polypeptide can be cross-linked with the polymer binder and the pore-forming agent through chain entanglement and hydrogen bond interaction to form a network structure. When deionized water is used for post-treatment: on the one hand, the pore-forming agent in the adsorbent particles will dissolve and diffuse into the deionized water, thereby forming a porous structure on the surface and inside of the particles. Due to the chain entanglement and hydrogen bond interaction between the polypeptide and the hydrophilic pore-forming agent, more hydrophilic pore-forming agents will be anchored on the surface of the porous structure, greatly improving the hydrophilicity of the adsorbent particle surface. On the other hand, under suitable water treatment temperature conditions, the residual carboxyl and amino groups of the polypeptide self-crosslink to form peptide bonds, which can provide stable and reversible crosslinking points between polymers, further enhancing the viscosity between the precursor powder and the polymer binder. Such an overall cross-linked network structure reduces the amount of binder used and increases the proportion of lithium adsorbent precursor powder, thereby greatly increasing the effective component ratio of the lithium adsorbent particles after molding. The polypeptide used in the present invention improves the hydrophilicity of the lithium adsorbent, making the adsorbent interact more strongly with brine, which is beneficial to increasing the lithium extraction rate and can make the lithium adsorbent precursor powder more firmly bonded, which is beneficial to improving the wear resistance and cycle life of the adsorbent. DETAILED DESCRIPTION
[0028] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the associated listed items.
[0030] The main sources of the examples and comparative examples of the present invention are as follows. Other raw materials and reagents can be obtained from commercial channels unless otherwise specified:
[0031] The lithium adsorbent precursor LiCl.2Al(OH)3.H2O is prepared by the method disclosed in the reference "Aluminium hydroxide as selective sorbent of lithium salts from brines and technical solutions";
[0032] Li 1.6 Mn 1.6 O4 was prepared by the method disclosed in the reference "Preparation of high manganese-lithium ratio adsorbent material and study of lithium adsorption performance";
[0033] Li2TiO3, tripeptide (copper peptide), and decapeptide-4 were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0034] The performance testing method in each embodiment of the present invention is as follows:
[0035] Adsorption capacity detection method: About 50g (dry weight) of adsorbent particles were loaded into glass chromatography columns respectively, and adsorption was carried out using brine from a salt lake with a high magnesium-lithium ratio (magnesium content 4g / kg, lithium content 0.2g / kg). The adsorption time was 1h, and then deionized water was used for desorption at room temperature for 1h. The adsorption capacity and desorption capacity were calculated based on the lithium ion concentration difference in the water sample.
[0036] Cycle service life evaluation method: According to the adsorption and desorption processes in the adsorption capacity detection method, simulate industrial continuous dynamic operation for 1000 cycles, and calculate the dissolution loss based on the mass difference of the adsorbent.
[0037] Example 1
[0038] Weigh 100g of lithium adsorbent precursor powder LiCl.2Al(OH)3.H2O, precursor powder particle size 50-100μm, 20g polyvinylidene fluoride, 2g tripeptide, 3g PVP K90 and 100g N,N-dimethylformamide, use a kneader to mix at 80°C for 5h to obtain a mixture, and then use a normal pressure drying oven to remove the solvent. The above mixture is crushed, and particles with a particle size of 0.5-3mm are sieved out. Stir with deionized water at 25°C at a rate of 120r / min for 48h, and filter out excess water to obtain a granular lithium adsorbent.
[0039] Example 2
[0040] Weigh 100g of lithium adsorbent precursor powder LiCl.2Al(OH)3.H2O, particle size 1-20μm, 5g polysulfone, 2.5g decapeptide-4, 0.5g PEG-2000 and 60g N,N-dimethylacetamide, use a kneader to mix at 100°C for 2h to obtain a mixture, and then use a normal pressure drying oven to remove the solvent. The above mixture is crushed, and particles with a particle size of 0.5-3mm are sieved out. It is stirred at 45°C with deionized water at a rate of 20r / min for 12h, and excess water is filtered out to obtain a granular lithium adsorbent.
[0041] Example 3
[0042] Weigh 100g of lithium adsorbent precursor powder LiCl.2Al(OH)3.H2O, particle size 20-50μm, 20g polyvinylidene fluoride, 2.5g tripeptide, 0.5g PEG-6000 and 120g N,N-dimethylformamide, use a kneader to mix at 120°C for 1.5h to obtain a mixture, and then use a normal pressure drying oven to remove the solvent. The above mixture is crushed, and particles with a particle size of 0.5-3mm are sieved out, and stirred at 35°C with deionized water at a rate of 70r / min for 24h, and excess water is filtered out to obtain a granular lithium adsorbent.
[0043] Example 4
[0044] Weigh 100g of lithium adsorbent precursor powder Li 1.6 Mn 1.6 O4, particle size 20-50 μm, 20 g polyvinylidene fluoride, 2.5 g decapeptide-4, 0.5 g PVP K30 and 80 g N-methylpyrrolidone, use a kneader to mix at 120 ° C for 1.5 hours to obtain a mixture, and then use a normal pressure drying oven to remove the solvent. The above mixture is crushed, and particles with a particle size of 0.5-3 mm are sieved out, and stirred at 35 ° C with deionized water at a rate of 70 r / min for 24 hours, and excess water is filtered out to obtain a granular lithium adsorbent.
[0045] Example 5
[0046] Weigh 100g of lithium adsorbent precursor powder Li2TiO3, particle size 20-50μm, 20g polyvinylidene fluoride, 2.5g decapeptide-4, 0.5g PEG-6000 and 120g N,N-dimethylformamide, use a kneader to mix at 120°C for 1.5h to obtain a mixture, and then use a normal pressure drying oven to remove the solvent. The above mixture is crushed, and particles with a particle size of 0.5-3mm are sieved out. Stir with deionized water at 70r / min for 24h at 35°C, and filter out excess water to obtain a granular lithium adsorbent.
[0047] Comparative Example 1
[0048] Weigh 100g of lithium adsorbent precursor powder LiCl.2Al(OH)3.H2O, particle size 20-50μm, 20g polyvinylidene fluoride, 0.5g PEG-6000 and 120g N,N-dimethylformamide, use a kneader to mix at 120°C for 1.5h to obtain a mixture. The above mixture cannot be formed into one piece, and there are still many lithium adsorbent precursor powders that cannot be bonded together. Use a normal pressure drying oven to remove the solvent and crush the mixture, sieve out particles with a particle size of 0.5-3mm, stir with deionized water at 70r / min at 35°C for 24h, filter out excess water, and obtain a granular lithium adsorbent.
[0049] Comparative Example 2
[0050] Weigh 100g of lithium adsorbent precursor powder Li2TiO3, with a particle size of 20-50μm, 20g of polyvinylidene fluoride, 0.5g of PEG-6000 and 120g of N,N-dimethylformamide, and mix them at 120°C for 1.5h using a kneader to obtain a mixture. The above mixture cannot be formed into one piece, and there are still many lithium adsorbent precursor powders that cannot be bonded together. Use a normal pressure drying oven to remove the solvent and crush the mixture, sieve out particles with a particle size of 0.5-3mm, stir with deionized water at 70r / min at 35°C for 24h, filter out excess water, and obtain a granular lithium adsorbent.
[0051] The adsorption and desorption capacity test results of the samples of Examples 1-5 and Comparative Examples 1-2 are as follows:
[0052] Lithium adsorption capacity (mg / g) Lithium desorption capacity (mg / g) Example 1 10.6 10.5 Example 2 9.2 9.2 Example 3 12.9 12.9 Example 4 11.8 11.8 Example 5 10.5 10.5 Comparative Example 1 7.4 7.4 Comparative Example 2 6.9 6.8
[0053] Using the sample of Example 3, the cycle life test results are as follows:
[0054]
[0055]
[0056] It can be seen from the table that the prepared granular lithium adsorbent has strong cycle stability, less dissolution loss, good wear resistance and cycle service life.
[0057] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.
Claims
1. A lithium adsorbent particle, characterized in that: The interior contains lithium adsorbent precursor powder, polypeptide, polymer binder and porogen.
2. The lithium adsorbent particle according to claim 1, characterized in that The lithium adsorbent precursor powder is selected from LiCl.2Al(OH)3.nH2O, LiMn2O4, Li 1.6 Mn 1.6 O4、Li 1.33 Mn 1.67 O4, Li2TiO3, Li4Ti5O 12 One or more of; preferably, the particle size of the lithium adsorbent precursor powder is 0.1-100μm, more preferably 1-50μm.
3. The lithium adsorbent particle according to claim 1 or 2, characterized in that: The polymer binder is selected from one or more of polysulfone, polyvinylidene fluoride, polyvinyl chloride, chlorinated polyvinyl chloride, cellulose acetate, carboxymethyl cellulose and chitosan.
4. The lithium adsorbent particle according to any one of claims 1 to 3, characterized in that: The mass ratio of the lithium adsorbent precursor powder to the polymer binder is 5 to 50:1, preferably 5 to 20:
1.
5. The lithium adsorbent particle according to any one of claims 1 to 4, characterized in that: The polypeptide is formed by dehydration condensation of 2 to 10 amino acids, and has a molecular weight of 200 to 1500; preferably, the mass ratio of the polypeptide to the polymer binder is 0.1 to 1:
1.
6. The lithium adsorbent particle according to any one of claims 1 to 5, characterized in that: The porogen is selected from one or more of PVPK30, PVP K60, PVP K90, PEG-1000, PEG-2000, and PEG-6000; preferably, the amount of the porogen is 0.1-5wt% of the mass of the lithium adsorbent precursor powder.
7. A method for preparing the lithium adsorbent particles according to any one of claims 1 to 6, characterized in that: The steps include: (1) mixing lithium adsorbent precursor powder, polypeptide, polymer binder, organic solvent and porogen uniformly to obtain a mixture; (2) curing, drying, crushing and screening the mixture to obtain a lithium adsorbent semi-finished product; (3) The lithium adsorbent semi-finished product is post-treated with water to obtain a granular lithium adsorbent.
8. The method for preparing lithium adsorbent particles according to claim 7, characterized in that: In step (1), the organic solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, chloroform, dichloroethane, and ethyl acetate; preferably, the amount of the organic solvent is 50 to 100% of the total mass of the lithium adsorbent precursor powder, polypeptide, and polymer binder.
9. The method for preparing lithium adsorbent particles according to claim 7 or 8, characterized in that: The mixing temperature in step (1) is 80-120° C., and the mixing time is 1-5 h. Preferably, in step (2), the particle size of the lithium adsorbent semi-finished product obtained by crushing and screening is 0.5 mm-3.0 mm. Preferably, in step (3), the post-treatment temperature is 25-45° C., and the time is 12-48 h. Preferably, the post-treatment process is accompanied by stirring, and the stirring rate is 20-120 r / min.
10. Use of the lithium adsorbent particles according to any one of claims 1 to 6 or the lithium adsorbent particles prepared by the preparation method according to any one of claims 7 to 9 in the field of lithium extraction from salt lakes.
Citation Information
Patent Citations
Preparation method of granular lithium adsorbent
CN109225124A
A method for preparing a lithium adsorbent and an apparatus for implementing the method.
CN115845825B
Porous composite lithium adsorbent and preparation method thereof
CN113996274A
Layered lithium adsorbent powder, preparation method, layered lithium adsorbent particles and application
CN116966867A
Novel process for extracting lithium from brine by utilizing temperature difference
CN117887979A
Cited By
Preparation method of high-strength lithium adsorbent
CN119926374A